Determinan terhadap Penyerapan Tenaga Kerja pada Sektor Industri di Kabupaten Merauke - Sebestina Siman; Esy Lewaherilla (Musamus Journal of Economics Development, 2020)
The purpose of this study is to analyze investment modalities, private investment and industrial businesses on the variable employment in Merauke Regency. Secondary data as the main data obtained from various sources had been conducted in Merauke Regency from 2013-2018. This type of research uses quantitative research that discusses hypotheses and explains the causal relationship between variables (explanatory research) between the effects of variables, namely exogenous variables to endogenous variables. Data analysis techniques from 2013-2018 as a time series (time series). Multiple linear regression with OLS (Ordinary Least Square) using the SPSS program. The results showed that the partial capital expenditure is negative and not significant to the labor absorption, for the investment value and positive and significant business units for the labor absorption in Merauke Regency. While the variable capital expenditure, investment value and business units are positive and significant to the labor absorption in Merauke Regency. Keywords: Capitala expenditure, private investment, industry, labor absorption